Everyday Security Practices in Gang-Controlled Neighborhoods in San Salvador - van der Borgh, Chris (Berghahn Journals, 2023)
This article looks at the everyday security practices of local residents in violent local orders, where capacities and strategies of state and non-state armed actors to produce regularity and stability are weak and contested. It discusses the case of gang-controlled neighborhoods in the metropolitan area of Greater San Salvador, El Salvador, in the years 2017–2018, when security “provision” of armed state and nonstate actors was weak and contested, and as a result civilians mostly took care of themselves. The article analyzes the main characteristics of local violent orders, the insecurity experiences of local residents, and the everyday practices of local residents to deal with these circumstances. It argues that in neighborhoods where security provision by state and non-state actors is weak and contested, everyday security practices of local residents are key to understanding the functioning and reproduction of the local forms of “disordered order.”
Keywords: Central America; everyday security practices; street gangs; violent local order